2022
DOI: 10.1021/acs.inorgchem.2c01354
|View full text |Cite
|
Sign up to set email alerts
|

Structural Complexity and Tuned Thermoelectric Properties of a Polymorph of the Zintl Phase Ca2CdSb2 with a Non-centrosymmetric Monoclinic Structure

Abstract: The Zintl phase Ca2CdSb2 was found to be dimorphic. Besides the orthorhombic Ca2CdSb2 (-o), here we report on the synthesis, the structural characterization, and the thermoelectric transport properties of its monoclinic form, Ca2CdSb2 (-m), and its Lu-doped variant Ca2–x Lu x CdSb2 (x ≈ 0.02). The monoclinic structure exhibits complex structural characteristics and constitutes a new structure type with the non-centrosymmetric space group Cm (Z = 30). The electrical resistivity ρ­(T) measured on single crystals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Although the value achieved at 600 K is close to that of Ca 10 SmCdSb 9 , a striking difference between these two phases lies in their electrical transport properties captured in Figure b,d. The degenerate semiconducting state in Ca 10 NdCdSb 9 makes it satisfy one of the important criteria of a good thermoelectric material candidate. This observation also attests to the fact that the structural/elemental configuration in the present case has resulted in near-optimal tuning conditions. This line of thought is further supported by the Hall coefficient measurements, which yield the following Hall concentrations n H at 300 K: 1.23 × 10 16 cm –3 (Ca 10 LuCdSb 9 ), 4.04 × 10 17 cm –3 (Ca 10 CeCdSb 9 ), 1.45 × 10 18 cm –3 (Ca 10 SmCdSb 9 ), and 4.68 × 10 20 cm –3 (Ca 10 NdCdSb 9 ).…”
Section: Resultssupporting
confidence: 60%
“…Although the value achieved at 600 K is close to that of Ca 10 SmCdSb 9 , a striking difference between these two phases lies in their electrical transport properties captured in Figure b,d. The degenerate semiconducting state in Ca 10 NdCdSb 9 makes it satisfy one of the important criteria of a good thermoelectric material candidate. This observation also attests to the fact that the structural/elemental configuration in the present case has resulted in near-optimal tuning conditions. This line of thought is further supported by the Hall coefficient measurements, which yield the following Hall concentrations n H at 300 K: 1.23 × 10 16 cm –3 (Ca 10 LuCdSb 9 ), 4.04 × 10 17 cm –3 (Ca 10 CeCdSb 9 ), 1.45 × 10 18 cm –3 (Ca 10 SmCdSb 9 ), and 4.68 × 10 20 cm –3 (Ca 10 NdCdSb 9 ).…”
Section: Resultssupporting
confidence: 60%
“…[36][37][38] This interest led to the rapid expansion of Zintl phases into the realm of transition and rare-earth elements; when such elements of open core-shells are incorporated, the attendant structural diversity and physical properties can reach new heights. 20,30,[39][40][41][42][43][44] The actualization of closed-shell electronic configuration in these materials brings about their characteristic features as semiconductors or insulators as well as the diamagnetic or temperature independent paramagnetic behavior. 26 The Zintl phases combine the features of narrow band gap, intricate atomic bonding and amenability to a high degree of disorder and present a fertile playground to explore the various electronic and transport properties of materials of interests ranging from the topological phases of matter 45,46 to applications in thermoelectrics 47 and photovoltaics.…”
Section: The Zintl Phasesmentioning
confidence: 99%
“…36–38 This interest led to the rapid expansion of Zintl phases into the realm of transition and rare-earth elements; when such elements of open core-shells are incorporated, the attendant structural diversity and physical properties can reach new heights. 20,30,39–44…”
Section: Introductionmentioning
confidence: 99%
“…Compounds with AM 2 Pn 2 and A 2 MPn 2 stoichiometry illustrate an example of the benefits and drawbacks of this generalized understanding of layered structures . Recent studies have emphasized the importance of cation bonding, identity, disorder, and defects in Yb 2 – x Ca x CdSb 2 , Ca 2 – x Eu x CdSb 2 , Yb 2– x Eu x CdSb 2 , Ca 2– x Lu x CdSb 2 , A 2 CdP 2 (A = Ba, Sr), and AZn 2 Sb 2 (A = Ca, Sr, Yb, Eu) in determining electronic properties and structure type. , In addition, studies on Mg 3 Sb 2 have revealed that the Zintl formalism does not adequately describe interactions between cations and [Mg 2 Sb 2 ] 2– slabs in AMg 2 Pn 2 compounds, which cannot be considered layered structures due to isotropic bonding networks, even though they adopt the CaAl 2 Si 2 structure type. , These examples highlight the need for better understanding of chemical bonding, defects, and local structure in each system to enable optimization of thermoelectric properties.…”
Section: Introductionmentioning
confidence: 99%